تأثير سلسلة التجهيز الرشيقة في تحقيق استدامة الأعمال: دراسة تحليلية في الشركة العامة لتصنيع الحبوب / بغداد - الجشعمي، كاظم أحمد جواد عباس; كاظم، إيمان فوزي (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2024)
يهدف البحث إلى دراسة تأثير سلسلة التجهيز الرشيقة بأبعادها (التسليم في الوقت المحدد، التحسين المستمر، القضاء على الهدر، التخزين الرشيق) في تحقيق استدامة الأعمال، إذ تواجه منظمات الأعمال اليوم عموما والشركة المبحوثة على وجه الخصوص ضغوط متزايدة من قوى تنافسية متنوعة وتشريعات قانونية مختلفة نتيجة لما تقوم به من أعمال يمكن أن يكون لها تأثيرا في البيئة ناتج عن أداءها، مما يتطلب منها أن تكون أكثر وعيا وادراك لما تقوم به من أعمال ونشاطات مختلفة خلال ممارسة عمليات الإنتاج، لذا لابد لها من أن تعمل على استخدام أساليب وأدوات معاصرة تساهم في الحد أو تخفيف تلك الضغوط والاستجابة إلى التوجهات العامة التي تفرض عليها، وتعد سلسلة التجهيز الرشيقة أحدى الأدوات المعاصرة في مجال إدارة الأعمال والتي يمكن من خلالها تحسين الأداء بتخفيض الهدر وأضافه القيمة من جهة وتعزيز الاستدامة في الأعمال من جهة أخرى، وتمثل مجتمع البحث بالشركة العامة لتصنيع الحبوب، وقد تم اختيار عينة قصدية مكونة من (70) فردا من مجتمع يتكون من (744) فردا، وتم توزيع استمارة الاستبيان عليهم، أسترجع منها (67) استمارة صالحة للتحليل الإحصائي، وبعد معالجة البيانات باستخدام البرنامج الإحصائي 26.SPSS V تم تحليل البيانات عن طريق استعمال الأساليب الإحصائية المناسبة، توصل البحث إلى مجموعة من النتائج من أهمها امتلاك الشركة المبحوثة لمستوى جيد من سلسلة التجهيز الرشيقة نتج عنه تأثير بمستوى عال ساهم في تحقيق استدامة الأعمال. The Research aims to study the impact of the lean supply chain with its dimensions (Just-in--time delivery, continuous improvement, waste elimination, lean storage) in achieving business sustainability, As today's business organizations in general and the researched company in particular are facing increasing pressures from various competitive forces and different legal legislations. As a result of the work that it does, it can have an impact on the environment as a result of its performance, which requires it to be more aware and aware of the different works and activities it performs during the practice of production operations. Therefore, it must work on using contemporary methods and tools that contribute to Reducing or alleviating those pressures and responding to the general trends that are imposed on them, and the lean supply chain is one of the contemporary tools in the field of business management through which it is possible to improve performance by reducing waste and adding value on the one hand and enhancing sustainability in business on the other hand, and it represents the research community of the company A sample of (70) individuals was chosen, and the questionnaire was distributed to them. of these, (67) forms valid for statistical analysis were retrieved. After processing the data using the SPSS V.26 statistical program, the data was analyzed by using statistical methods. On this occasion, the research reached a set of results, the most important of which is that the researched company possesses a good level of agile supply chain, which resulted in a high level of impact that contributed to achieving business sustainability.
Keywords: سلسلة التجهيز الرشيقة -- المؤسسات الصناعية -- التنمية المستدامة -- العراق